Evaluating hepatoprotective activity of polyherbal formulations- an overview of dietary antioxidants - Mochahary, Banjai; Middha, Sushil Kumar; Usha, Talambedu; B. N. Nagalaxmi; Goyal, Arvind Kumar (Plant Science Today, 2023)
Chronic liver disease is the foremost cause of morbidity, accounting for 2.2 percent of death. In recent years, excessive attention has been focused on using natural antioxidants as they have the potential to minimize oxidative stress in cells and thus help treat various ailments. Some scientists estimate that two-thirds of plant species have medical applications, and many of these have significant antioxidant potential. Polyherbal formulations (PHFs) have shown therapeutic promise in the treatment of several acute and chronic conditions, including diabetes, wound care, hypertension, cardiovascular disorders, anxiety, neurological imbalances, and disorders of the gastrointestinal, respiratory, and endocrine systems. This article reviews the antioxidant potential of the various polyherbal formulations developed to treat hepatic disorders during the past ten years. After preliminary screening, 53 abstracts based on the polyherbal formulations selected for hepatoprotection were retrieved from several bibliographical databases. This review provides insight and indicates the gaps presented in the case of polyherbal formulations (PHFs) formulations. To conclude, PHFs can activate several physiological processes that quicken the process. Clinical trials should be conducted to further examine these PHFs, and production upscaling will help to open up new markets for PHFs.